In vivo pharmacokinetics of Glycyrrhiza uralensis polysaccharides - Wubuli, Abudukahaer; Chai, Junwei; Liu, Haoqiang; Nijat, Dilaram; Li, Jianmin; Xia, Guoyu; Cao, Qi; Zhang, Saidan; Huang, Weidong; Aipire, Adila; Li, Jinyao (Frontiers in Pharmacology, 2024)
Glycyrrhiza uralensis polysaccharides (GUPS) are widely applied in biomedicine and functional food due to their multiple pharmacological activities and low toxicity. Despite their widespread use, the in vivo metabolic profile of GUPS remains poorly understood. To address this gap, we developed a quantitative analysis method that involves labeling GUPS with visible fluorescein (5-DTAF) and near-infrared (NIR) fluorescein (Cy7), resulting in stable conjugates with substitution degrees of 0.81% for 5-DTAF and 0.39% for Cy7. The pharmacokinetic studies showed a biphasic elimination pattern in the blood concentration-time curve following both intravenous and oral administration, consistent with a two-compartment model. Using fluorescence quantification and NIR imaging, we observed that GUPS was distributed to various tissues, exhibiting higher concentrations particularly in liver, kidney and lung. Excretion studies indicated that feces were the major excretion pathway of GUPS after oral administration (60.98%), whereas urine was the main pathway after intravenous administration (31.16%). Notably, GUPS could be absorbed rapidly by gut (Tmax 1±0.61 h) and showed a biological half-time t1/2 26.4±7.72 h after oral administration. Furthermore, the Caco-2 cells uptake studies illustrated that macropinocytosis and clathrin-mediated endocytosis were participated in the transport of GUPS in intestine epithelium. This comprehensive analysis of the in vivo pharmacokinetics of GUPS not only enhances our understanding of its metabolic pathways but also establishes a foundational basis for its clinical application, optimizing its therapeutic potential and safety profile.